Human Visceral Adipose Tissue Macrophages Are Not Adequately Defined by Standard Methods of Characterization - Alecia M. Blaszczak; Anahita Jalilvand; Joey Liu; Valerie P. Wright; Andrew Suzo; Bradley Needleman; Sabrena Noria; William Lafuse; Willa A. Hsueh; David Bradley (Journal of Diabetes Research)
Obesity is associated with a state of chronic low-grade inflammation both systemically and within specific tissues, including adipose tissue (AT). In murine models of obesity, there is a shift in the inflammatory profile of the AT immune cells, with an accumulation of proinflammatory M1 macrophages that surround the expanding adipocyte. However, much less is known about the immune cell composition and how to best define AT macrophages in humans. Objective. The goals of the current study were to determine the contribution of macrophages to the stromal vascular fraction (SVF) in lean versus obese human visceral AT (VAT); examine the expression of common M1, M2, and pan macrophage markers; and determine the association of specific macrophage types with known biomarkers of obesity-related cardiometabolic disease. Research Design and Methods. VAT biopsies were obtained from obese (n=50) and lean (n=8) patients during elective surgery. Adipocytes and SVF were isolated, and the SVF was subjected to flow cytometry analyses. Results. Our results indicate that VAT macrophages are increased in obesity and associate with biomarkers of CVD but that many macrophages do not fall into currently defined M1/M2 classification system based on CD206 receptor expression levels. Conclusions. VAT macrophages are increased in obese subjects, but the current markers used to define macrophage populations are inadequate to distinguish differences in human obesity. Further studies are needed to delineate the function of AT macrophages in the maintenance and progression of human AT inflammation in obesity.